EVALUASI SANITASI DAN KEBERADAAN VEKTOR PADA KAPAL BARANG DAN KAPAL PENUMPANG DI PELABUHAN TANJUNG EMAS SEMARANG - Intan Aulia Putri; Tri Joko; Niki Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Ship sanitation is very important because it can prevent and minimize the presence of vector as the cause of disease transmission like Leptospirosis and Cholera. A proper evaluation by the Port Health Office, especially the Environmental Risk Control Section as the technical implementation of of ship sanitation inspection. This study aims to determine the condition of hygiene, sanitation, and the presence of vector on the cargo and passenger ship in Tanjung Emas Port. This research was an observational study with cross sectional approach. The sample of this research was 16 ship consisting of 12 cargo ship and 4 passenger ship that have an inspection schedule on May 31 – June 11 2017. The results of this study indicate that there are some variables that unqualified, they are kitchen sanitation (6,25%), kitchen lighting (6,25%), washing facilities in the kitchen (100%), solid waste management (6,25%), and presence of vectors (14,5%). The conclusion of this study are there are ships that have unquilified room sanitation and solid waste management, also be found ships with high risk categories.